Leadership Style on Job Satisfaction Moderated by Employee Commitment - Sharifah Norasykin Said Madeen@Syed Nordina; Sidah Idris (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
Leadership is the process or ability of a person to lead, direct, and influence other people or a group of people in achieving a certain goal or vision. Leadership involves various aspects, including decision making, communication, problem solving, motivation, and developing a vision or direction for an organisation or group. The objective of this study is to evaluate the leadership style that can be adopted by a leader. This study will be conducted to examine the relationship between leadership style and job satisfaction for different groups of employees. This study will explore whether the effect of leadership style on job satisfaction is stronger for employees with high work commitment compared to those with low work commitment. The scope of this study is for individuals who work in service and real estate companies. At the beginning of this study, this article will use literature review to find the research gap in this field whether local or international. It is hoped that the results of the study in this writing will be able to provide evidence to the gaps in previous studies. This study will be carried out by providing analysis to individuals involved as department or company leaders. The significance of this study will be able to prove that the issue of leadership is a broad and important topic in aspects of life, and the understanding of what leadership is can vary according to the context and approach used in the organisation.